A novel tree-shaped ground heat exchanger for GSHPs in severely cold regions. (5th January 2019) - Pu, Liang; Xu, Lingling; Qi, Di; Li, Yanzhong
Highlights: A novel tree-shaped GHE for GSHPs in severely regions was proposed. A comparison study between tree-shaped and serpentine-shaped GHE was studied. The tree-shaped GHE efficiently eliminate thermal load imbalance of GSHPs. Effects of bifurcation angle and bifurcation number on performance of GHE. Abstract: In severely cold regions, thermal load imbalance and fluctuation of soil temperature always occur in the application of ground source heat pump system (GSHPs), resulting in the degradation of thermal efficiency and even the collapse of the overall GSHPs. In this study, a novel tree-shaped ground heat exchanger (GHE) is suggested for GSHPs in severely cold regions instead of common type: serpentine-tube type to mitigate soil temperature fluctuation and obtain a better comprehensive performance. In the analysis, to investigate the potential of tree-shaped GHE, a comparison study between tree-shaped and serpentine-shaped GHE is carried out. Furthermore, the optimizations of different structure parameters for tree-shaped GHE are studied. The results indicate that the tree-shaped GHE is propitious to weaken soil temperature fluctuation. Meanwhile, the tree-shaped GHE shows a 33.4–38.3% higher comprehensive performance and yields a 51.2–56% lower pressure drop than serpentine-tube type at the inlet-velocity of 0.4–1.2 m/s. Taking integrative performance of GHE into account, the optimal bifurcation angle is 120 ∘ .